Cell Type Impacts Accessibility of mRNA to Silencing by RNA Interference - Chantal M. Ferguson; Dimas Echeverria; Matthew Hassler; Socheata Ly; Anastasia Khvorova (Elsevier, 2020)
RNA interference (RNAi) is a potent mechanism that silences mRNA and protein expression in all cells and tissue types. RNAi is known to exert many of its functional effects in the cytoplasm, and thus, the cellular localization of target mRNA may impact observed potency. Here, we demonstrate that cell identity has a profound impact on accessibility of apolipoprotein E (ApoE) mRNA to RNAi. We show that, whereas both neuronal and glial cell lines express detectable ApoE mRNA, in neuronal cells, ApoE mRNA is not targetable by RNAi. Screening of a panel of thirty-five chemically modified small interfering RNAs (siRNAs) did not produce a single hit in a neuronal cell line, whereas up to fifteen compounds showed strong efficacy in glial cells. Further investigation of the cellular localization of ApoE mRNA demonstrates that ApoE mRNA is partially spliced and preferentially localized to the nucleus (∼80%) in neuronal cells, whereas more than 90% of ApoE mRNA is cytoplasmic in glial cells. Such an inconsistency in intracellular localization and splicing might provide an explanation for functional differences in RNAi compounds. Thus, cellular origin might have an impact on accessibility of mRNA to RNAi and should be taken into account during the screening process.